Performance Analysis of A New Mechanism Of 2.4 GHz Embedded Active RFID Based WSN Location Tracking and Monitoring System - Poad, F. A.; Ismail, W.; Jusoh, J. F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper describes the experiments and analysis conducted on a new mechanism of 2.4 GHz embedded active Radio Frequency Identification (RFID) – Wireless Mesh Sensor Network (WMSN) based system that has been developed for the purposes of location tracking and monitoring in indoor and outdoor environments. Several experiments are conducted to test the effectiveness and performance of the developed system such as the Radio Frequency (RF) transmitting power, Received Signal Strength Indicator (RSSI), tags collection time (latency) and throughput to prove that the embedded active RFID tag is capable to provide better performance compared to standalone RFID tag. Experiments are carried out on three RFID tags which are active RFID tag embedded with Global Positioning System (GPS) and Global System for Mobile (GSM) (ERFIDG2); active RFID tag embedded with Global Positioning System (GPS) (ERFIDG) and standalone RFID tag communicating with the same active RFID reader. The developed ERFIDG2 contributes 9.14 % transmit power and 13.79 % RSSI reading higher than standalone RFID tag. In addition, the tags collection time (latency) is 7.14 % slower than the standalone RFID, while the throughput is 6.62 % lower than the standalone RFID over multihop communication. The results conclude that the ERFIDG2 gives better performance compared to standalone RFID tag and can be used as guidelines for future design improvements.